Pheochromocytoma and paraganglioma: molecular testing and personalized medicine. Issue 1 (January 2016) - Burnichon, Nelly; Buffet, Alexandre; Gimenez-Roqueplo, Anne-Paule
Abstract : Purpose of review: Pheochromocytomas and paragangliomas (PPGLs) are rare tumours, strongly associated with inherited susceptibility gene mutations, and presenting limited therapeutic options for patients with metastatic disease. This review discusses the recent developments in the characterization of PPGL genetic heterogeneity and associated tumorigenesis pathways, together with their potential clinical relevance. Recent findings: The mutational landscape of PPGL is now well defined, especially with the contribution of next-generation sequencing. Up to 70% of these tumours harbour a germline or a somatic mutation in one of the numerous predisposing genes. In parallel, 'omics' analyses have identified mutation-linked subsets of tumours substantially associated with molecular signatures suggesting new therapeutic targets for patients with a malignant transformation of the disease. Summary: In the near future, extended molecular testing of PPGL could be used to determine therapeutic approaches and assess diagnosis and prognosis biomarkers. Considering the current development of next-generation sequencing-based genetic screening, this technology appears as a good option to improve both PPGL molecular diagnosis and patient management.